2021
DOI: 10.1186/s12876-021-01973-5
|View full text |Cite
|
Sign up to set email alerts
|

Risk and characteristics of tuberculosis after anti-tumor necrosis factor therapy for inflammatory bowel disease: a hospital-based cohort study from Korea

Abstract: Background Anti-tumor necrosis factor (TNF) treatment for inflammatory bowel disease (IBD) increases the risk of tuberculosis (TB) infection. In the present study, we analyzed the clinical characteristics and risks of TB in Korean patients with IBD who received anti-TNF treatment. Methods The study included patients with IBD who were treated using anti-TNF agents between January 2001 and June 2018 at the Asan Medical Center. Overall, 1434 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
1
2
0
1
Order By: Relevance
“… 11 Additionally, we recently reported that from 2001 to 2018, 1.46% (21/1,434) patients who received TNF inhibitors at our center developed active tuberculosis during the mean follow-up period of 49 months. 13 During the same period as this study (from 2017 to 2020), we also found that four (0.7%) patients were diagnosed with active tuberculosis among 582 patients treated with TNF inhibitors at least once. The median interval between the TNF inhibitor initiation and the diagnosis of active tuberculosis in these four patients was 7.0 months (IQR, 3.5–10.5).…”
supporting
confidence: 69%
“… 11 Additionally, we recently reported that from 2001 to 2018, 1.46% (21/1,434) patients who received TNF inhibitors at our center developed active tuberculosis during the mean follow-up period of 49 months. 13 During the same period as this study (from 2017 to 2020), we also found that four (0.7%) patients were diagnosed with active tuberculosis among 582 patients treated with TNF inhibitors at least once. The median interval between the TNF inhibitor initiation and the diagnosis of active tuberculosis in these four patients was 7.0 months (IQR, 3.5–10.5).…”
supporting
confidence: 69%
“…As TNF plays a pivotal role in the formation and maintenance of granuloma integrity, 14 there is an increased risk of active tuberculosis with anti-TNF-α agent use that varies by geographical variation in tuberculosis burden 36 South Korea has a intermediate incidence of tuberculosis (36/100,000 per year in 2021), 37 so patients with IBD in South Korea who are treated with anti-TNF-α agents face a higher risk of tuberculosis than those in Western countries. 38 , 39 In contrast, as the mechanism of action of ustekinumab is indirectly related to the inhibition of TNF and the drug target of vedolizumab is not associated with TNF, 40 the risk of tuberculosis associated with these drugs appears to be theoretically lower than that associated with the anti-TNF-α agents. Previous studies have reported that the risk of active tuberculosis is considerably lower in patients with IBD who receive vedolizumab or ustekinumab 18 , 41 , 42 and the rate of active tuberculosis also tended to be lower in patients treated with vedolizumab or ustekinumab in our study cohort.…”
Section: Discussionmentioning
confidence: 99%
“…El riesgo de reactivación de TBC latente con el uso de otros biológicos con diferentes mecanismos de acción como bloquear la integrina α4β7 (vedoluzimab) o bloquear el anti p40 de la ruta de presentación de la IL 12/23 (Ustekinumab) es lo recomendado por las guías (16)(17) . El estudio de Lee et al muestra una tasa de incidencia de TBC en pacientes con EII tratados con agentes anti-TNF de 366 por 100 000 personas al año, y la prevalencia fue de 1,46% (18) . Los reportes actuales confirman 2 a 6 veces más riesgo de tasa de reactivación de TBC en pacientes que reciben anti-TNF (19) (infliximab o adalimumab); comparado con un riesgo bajo o nulo para ustekinumab (20,21) .…”
Section: Discussionunclassified